Book Review. Why Constant False Alarm Rate? - Ivan Popchev (International Journal Bioautomation, 2025)
Thе book presents the algorithms that ensure the maintenance of a constant false alarm rate (CFAR detectors) in the detection of radar targets in conditions of an intensively noisy environment. This type of detectors uses an adaptive threshold dependent on the disturbance level, thus ensuring that a constant false alarm probability is kept. The rapid development of algorithms in this area in recent years can be explained both by the very pronounced need in various fields of science and technology to automatically perform the procedure of detecting a useful signal against the background of disturbances, and by the theoretical interest to interpret the classical approaches to the detection tasks in a modern way.